RNA-Seq Provides Novel Genomic Resources for Noug (Guizotia abyssinica) and Reveals Microsatellite Frequency and Distribution in Its Transcriptome - Gebeyehu, Adane; Hammenhag, Cecilia; Tesfaye, Kassahun; Vetukuri, Ramesh R.; Ortiz, Rodomiro; Geleta, Mulatu (Frontiers in Plant Science, 2022)
Genomic resources and tools are essential for improving crops and conserving their genetic resources. Guizotia abyssinica (noug), an outcrossing edible oilseed crop, has highly limited genomic resources. Hence, RNA-Seq based transcriptome sequencing of 30 noug genotypes was performed to generate novel genomic resources and assess their usefulness. The genotypes include self-compatible and self-incompatible types, which differ in maturity time, photoperiod sensitivity, or oil content and quality. RNA-Seq was performed on Illumina HiSeq 2500 platform, and the transcript was reconstructed de novo, resulting in 409309 unigenes. The unigenes were characterized for simple sequence repeats (SSRs) and served as a reference for single nucleotide polymorphism (SNP) calling. In total, 40776 SSRs were identified in 35639 of the 409309 unigenes. Of these, mono, di, tri, tetra, penta and hexanucleotide repeats accounted for 55.4%, 20.8%, 21.1%, 2.3%, 0.2% and 0.2%, respectively. The average G+C content of the unigenes and their SSRs were 40% and 22.1%, respectively. The vast majority of mononucleotide repeat SSRs (97%) were of the A/T type. AG/CT and CCA/TGG were the most frequent di and trinucleotide repeat SSRs. A different number of single nucleotide polymorphism (SNP) loci were discovered in each genotype, of which 1687 were common to all 30 genotypes and 5531 to 28 of them. The mean observed heterozygosity of the 5531 SNPs was 0.22; 19.4% of them had polymorphism information content above 0.30 while 17.2% deviated significantly from Hardy-Weinberg equilibrium (P < 0.05). In both cluster and principal coordinate analyses, the genotypes were grouped into four major clusters. In terms of population structure, the genotypes are best represented by three genetic populations, with significant admixture within each. Genetic similarity between self-compatible genotypes was higher, due to the narrow genetic basis than that between self-incompatible genotypes. The genotypes that shared desirable characteristics, such as early maturity, and high oil content were found to be genetically diverse, and hence superior cultivars with multiple desirable traits can be developed through crossbreeding. The genomic resources developed in this study are vital for advancing research in noug, such as genetic linkage mapping and genome-wide association studies, which could lead to genomic-led breeding.